Human resource management surveys at organizations operating at profitoriented and public spheres - Gergely, Éva (Acta Agraria Debreceniensis, 2009)
I introduce the performance management from the area of human resource management that I examined at organizations operating in market environment and in the public sphere as well. The reason of my choice of subject is that the performance management got into the centre of interest also in Hungary lately. The scale of values connecting traditionally to the organizations of the private and public sphere is different vitally, what affected substantive differences of the organization, the management and the human resources management environment. Within these I tried to reveal their performance management system and with their comparison to draw conclusions. I did my surveys at profit oriented organizations and at organizations operating at the public sphere. Performance management is one centre field of modern human resource managing, as the basis of the successful functioning of any company is the possibly most effective operation of its resources. Performance management is a possibility for the company and for the employer to overview the realization of the determined aims and the factors that block or promote accomplishments. Considering the results, the employee and the manager could determine subsequent realistic and accessible aims for the following period. Achievement management is extremely important in those positions where achievement could not be measured accurately. I carried out my surveys according to performance management by observation and data acquisition. I applied questionnaire survey to collect data, or rather made deep interviews; I talked personally with more employees as well. The questionnaire consisted of one data format and performance management questionnaire. I processed the gathered data by computer and visualized graphically. I also did examinations by using statistic methods, by which I was able to get to know the certain organizations deeper and thus it was possible for me to reveal more connections.